2017
DOI: 10.1681/asn.2016121362
|View full text |Cite
|
Sign up to set email alerts
|

Redirecting TGF-β Signaling through the β-Catenin/Foxo Complex Prevents Kidney Fibrosis

Abstract: TGF- is a key profibrotic factor, but targeting TGF- to prevent fibrosis also abolishes its protective anti-inflammatory effects. Here, we investigated the hypothesis that we can redirect TGF- signaling by preventing downstream profibrotic interaction of -catenin with T cell factor (TCF), thereby enhancing the interaction of-catenin with Foxo, a transcription factor that controls differentiation of TGF- induced regulatory T cells (iTregs), and thus, enhance anti-inflammatory effects of TGF- In iTregs derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 44 publications
4
71
0
3
Order By: Relevance
“…Joo et al confirmed that sitagliptin can restore Foxo3a activity and reduce renal structural and functional impairment by reducing the ratio of P‐Foxo3a/total Foxo3a in 5/6 nephrectomy rats. Further studies by Qiao et alconfirmed that ICG‐001's targeted blockage of β‐catenin/TCF signalling activation induced by TGF‐β1 can promote β‐catenin/Foxo binding, inhibit TGF‐β1‐induced renal fibrosis, and enhance the anti‐inflammatory activity of TGF‐β1. However, whether the sitagliptin‐mediated protective effect in the kidney via blocking high glucose‐induced Wnt/β‐catenin signalling is related to the enhanced Foxo activity resulting from the inhibition of β‐catenin‐induced TCF signalling requires further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Joo et al confirmed that sitagliptin can restore Foxo3a activity and reduce renal structural and functional impairment by reducing the ratio of P‐Foxo3a/total Foxo3a in 5/6 nephrectomy rats. Further studies by Qiao et alconfirmed that ICG‐001's targeted blockage of β‐catenin/TCF signalling activation induced by TGF‐β1 can promote β‐catenin/Foxo binding, inhibit TGF‐β1‐induced renal fibrosis, and enhance the anti‐inflammatory activity of TGF‐β1. However, whether the sitagliptin‐mediated protective effect in the kidney via blocking high glucose‐induced Wnt/β‐catenin signalling is related to the enhanced Foxo activity resulting from the inhibition of β‐catenin‐induced TCF signalling requires further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Kidney-derived klotho is of particular interest as a potential treatment for inflammation and premature ageing in CKD, because klotho-deficient mice and patients with CKD have similar phenotypes, such as EVA and a pro-inflammatory status, and klotho is related to ageing in both humans and mice [70,72]. Similar to the NRF2 system, klotho is repressed in CKD, and stimulation of klotho can ameliorate oxidative stress and mitochondrial function [108], renal fibrosis [152], inflammation [72], as well as premature ageing [108], including EVA [55,[81][82][83][111][112][113].…”
Section: Klotho Pathwaymentioning
confidence: 99%
“…The contrasting effects of TGF-β (profibrotic versus anti-inflammatory) have posed a considerable challenge in the treatment of fibrotic diseases affecting the kidneys and other organs. However, we have recently described the role of β-catenin/Foxo in the redirection of TGF-β signaling from an undesirable profibrotic to a beneficial anti-inflammatory function [6].…”
Section: Introductionmentioning
confidence: 99%